2015
DOI: 10.1097/aog.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone With Buccal Misoprostol for Medical Abortion

Abstract: OBJECTIVE:To summarize clinical outcomes and adverse effects of medical abortion regimens consisting of mifepristone followed by buccal misoprostol in pregnancies through 70 days of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
83
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 30 publications
18
83
2
1
Order By: Relevance
“…Although the medical abortion efficacy rates were similar in both groups, the overall efficacy is lower (93.4%) compared to what we expected using evidence-based regimens [1,2,16]. The ongoing pregnancy rate of 1.2% is similar to previous studies; however, the incomplete abortion rate in this study was higher.…”
Section: Discussioncontrasting
confidence: 54%
“…Although the medical abortion efficacy rates were similar in both groups, the overall efficacy is lower (93.4%) compared to what we expected using evidence-based regimens [1,2,16]. The ongoing pregnancy rate of 1.2% is similar to previous studies; however, the incomplete abortion rate in this study was higher.…”
Section: Discussioncontrasting
confidence: 54%
“…These issues became evident during data collation for creation of the 2014 Medical Management of First Trimester Abortion Practice Bulletin written collaboratively by the American College of Obstetricians and Gynecologists and the Society of Family Planning [6,7]. More recently, a systematic review including approximately 30,000 patients who received mifepristone and buccal misoprostol found that only 57% had data identifying week of gestation for a stratified evaluation of overall efficacy; only 51% had such information for evaluation of continuing pregnancy [9].…”
Section: Introductionmentioning
confidence: 99%
“…With a regimen of mifepristone and vaginal misoprostol, approximately 3% to 5% of women will subsequently undergo uterine evacuation [1][2][3]. Regimens using mifepristone and buccal misoprostol have a similar (3.3%) risk of requiring uterine evacuation [4,5]. In approximately 2%-3% of women, uterine evacuations are performed after expulsion of the pregnancy due to pain or bleeding [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%
“…Regimens using mifepristone and buccal misoprostol have a similar (3.3%) risk of requiring uterine evacuation [4,5]. In approximately 2%-3% of women, uterine evacuations are performed after expulsion of the pregnancy due to pain or bleeding [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%